Processos existenciais em reportagens de capa da revista superinteressante - Lima, Lauro Rafael (2013)
This dissertation has as theme the study of the existential processes from the transitivity system of the systemic-functional grammar (HALLIDAY & MATTHIESSEN, 2004). This functionalist approach understands language as a system that can be stratified and categorized. In view of this possibility, that works at the same time with numerical data and whit analysis and interpretation of the findings in a given context. The main objective of this research is to identify the verbs that can constitute existential processes, both prototypical as other verbs, in a corpus of sixteen (16) cover reports of the Superinteressante magazine, been eight (8) reports with a scientific thematic and eight (8) with a historical thematic. In the beginning we created a wordlist, with the assistance of the tool Word Smith (SCOTT, 2008), selected all the verbs that may function as existential processes and analyzed all the occurrences. The fifteen (15) most frequent verbs were analyzed in this research. The results point to the prevalence of the verbs there is and to exist in science reports, and to die and to born in historical reports. The Existents, more frequently function in thematic position, are mostly not conscious beings. Few are the Existents that refer to persons. The verb to have , typical of the Brazilian spoken language, is used with the sense of to exist and has it‟s Existent always in rhematic position. These results can contribute to the existential processes description in the Halliday‟s perspective. From this, we interpreted the contribution of the existential processes to the report genre (BONINI, 2003; LAGE, 1987; MELO, 1994) according to the Superinteressante magazine‟s thematics.